A small heterobifunctional ligand provides stable and water dispersible core–shell CdSe/ZnS quantum dots (QDs). Issue 42 (26th September 2018) - Salerno, Gianluca; Scarano, Simona; Mamusa, Marianna; Consumi, Marco; Giuntini, Stefano; Macagnano, Antonella; Nativi, Stefano; Fragai, Marco; Minunni, Maria; Berti, Debora; Magnani, Agnese; Nativi, Cristina; et al.
Abstract : A small heterobifunctional ligand provides easy to handle and hydrophilic QDs with enhanced colloidal stability. Abstract : We describe a simple method to prepare water dispersible core–shell CdSe/ZnS quantum dots (QDs)1 by capping QDs with a new thiol-containing heterobifunctional dicarboxylic ligand4 (DHLA-EDADA). This ligand, obtained on a gram scale through a few synthetic steps, provides a compact layer on the QDs, whose hydrodynamic size in H2 O is 15 nm ± 3 nm. The colloidal stability is dramatically enhanced with respect to the well-known (±) α-lipoic acid (DHLA). The ligand affinity towards QDs and the water dispersibility of nanocrystals1 are addressed by the dithiol groups of DHLA, which chelate the zinc of the shell, and by the dicarboxylic groups of the ethylenediamine- N, N -diacetic acid (EDADA) residue, respectively. The effects of pH, buffer solutions, and biological medium on the stability of QDs1 were assessed by monitoring the photoluminescence (PL) and hydrodynamic size over time. Highly fluorescent QD dispersions, stable over extended periods of time and over broad pH ranges and buffer types, were obtained. Furthermore, we show that the DHLA-EDADA ligand4 also endows QDs with functional groups suitable for further conjugation and for metal ion detection. As a case study to illustrate the potential of our approach, we report the preparation and characterization of a highly luminescent orange light emitting polymer-QD1 composite film.